Persembuhan luka incisi kulit mencit (Mus musculus) dengan pemberian ekstrak etanol teripang getah (Holothuria leucospilota) - Srivikaya R.W. Ollu; Putri Pandarangga; Nemay A. Ndaong (Jurnal Veteriner Nusantara, 2019)
The purpose of this research is to compare the effect of the ethanol black sea cucumber (Holothuria leucospilota) extract with betadine in the healing wound process of incised skin of mice (Mus musculus) through observation of gross pathology and histopathology. This research used mice with age of 6-8 weeks, male and divided into three groups, which were negative control (aquades), the positive control (betadine), and the treatment (ethanol black sea cucumber extract). All mice were incised by surgical blade in the middle of the back with the depth of up to layer of dermis. Furthermore, the wounds were lubricated directly by aquades, betadine and ethanol black sea cucumber extract. The gross pathology data were obtained in eight days through the observation of color, dry cuts, the closing time, the scab formation and the increase the length of hair around and the wound size. The parameters used in histopathology analysis of healing wounds process were the presence of increasing number of cells fibroblast, angiogenesis, and the number of the inflammation cells around the wound. The results showed that the effect of ethanol black sea cucumber (H. leucospilota) extract accelerated the wound healing process in the incised skin of mice (Mus musculus). It was caused by the bioactive content of black sea cucumber, such as saponin, flavonoid, lectin and amino acids which can speed up wound healing wound.